Factors influencing the home preparation and consumption of seafood amongst seniors living independently - McManus, Alexandra; Hunt, Wendy; Russell-Weisz, L.; McManus, J. (Curtin, 2014)
This study investigated the barriers and enablers to seafood and fish consumption and the knowledge, attitudes and perceptions of fish and seafood consumption amongst independently living seniors. The information collected will be used to develop of a series of nutritionally balanced meals suitable for seniors using a variety of fish and seafood species.